1965
DOI: 10.1111/j.1476-5381.1965.tb01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Medullary Amines From the Isolated Perfused Adrenal Gland of the Dog

Abstract: In a previous paper (Muscholl & Vogt, 1964) the release of catechol amines from extramedullary chromaffin tissue had been examined, and certain differences found between the responses of extramedullary chromaffin cells perfused with Locke solution and the well-known reactions of the adrenal medulla in situ. Thus electrical stimulation of preganglionic fibres to the ganglion containing the chromaffin tissue did not cause a release of adrenaline or noradrenaline, as does stimulation of the nerve supply to the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1

Year Published

1965
1965
1972
1972

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
(12 reference statements)
3
10
1
Order By: Relevance
“…Reserpine does not release amines from the perfused adrenal medulla (Vogt, 1965). If the release caused by prenylamine is regarded as an artefact, the absence of action on the adrenal medulla would represent one more instance in which the two substances resemble each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reserpine does not release amines from the perfused adrenal medulla (Vogt, 1965). If the release caused by prenylamine is regarded as an artefact, the absence of action on the adrenal medulla would represent one more instance in which the two substances resemble each other.…”
Section: Resultsmentioning
confidence: 99%
“…Dog isolated adrenal glands were perfused by gravity at 350 C with Locke solution gassed with a stream of 5% carbon dioxide and 95% oxygen. Details of the dissection are published elsewhere (Vogt, 1965). Difficulties were encountered by cloudiness forming when the 5%, prenylamine gluconate was diluted with Locke solution; this was prevented by diluting with bicarbonatefree Locke solution, saturating the mixture with 5% carbon dioxide and 95% oxygen, and adding the bicarbonate last.…”
mentioning
confidence: 99%
“…Thus, although electrical stimulation of the cat's hypothalamus altered the composition of the catecholamines secreted from the adrenal glands (Folkow & von Euler, 1954) and, in the dog, electrical stimulation of the splanchnic nerves innervating the adrenal gland (either intact or perfused) changed the composition of the catecholamines released from the gland (Mirkin, 1961 ;Vogt, 1965), no effective regulation of the amount of these amines was found in the dog by Lund (1951). Experiments on the perfused adrenal glands of cats have shown that pilocarpine, histamine, muscarine and polypeptides such as bradykinin, kallidin and angiotensin elicited a preferential release of adrenaline when added to the perfusion medium; nicotine and KCl released principally noradrenaline (Rubin & Miele, 1968;StaszewskaBarczak & Vane, 1967).…”
Section: Preferential Catecholainine Secretion In Vivomentioning
confidence: 99%
“…The poor response of the adrenal medulla of more mature calves was particularly surprising in view of the previous reports of peptide-induced secretion in other species (Feldberg & Lewis, 1964, 1965StaszewskaBarczak & Vane, 1965, 1967Piper & Vane, 1967). In the present experiments the amounts of noradrenaline and adrenaline released by angiotensin and bradykinin were only marginally above the resting output from the medulla, whereas stimulation of the splanchnic nerve or the injection of acetylcholine induced a 10-100 fold increase in output.…”
Section: Discussionmentioning
confidence: 97%
“…The cause of this increased sensitivity, which lasts for a considerable time, is unknown. It is possible that peptides such as bradykinin or angiotensin could be involved, for reports of their potent action on the adrenal medulla of the adult rabbit (Lecomte, Troquet & Dresse, 1961), cat (Feldberg & Lewis, 1964, 1965, dog (Staszewska-Barczak & Vane, 1965, 1967 and guinea-pig (Piper & Vane, 1967) suggested that these peptides might be necessary for the release of stored catecholamines. The effects of bradykinin and angiotensin on the adrenal medulla have therefore been examined in young calves 24 hr after birth and have been compared with results obtained in more mature animals and in adult cats.…”
Section: Introductionmentioning
confidence: 99%